(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
The study examined the challenges encountered by teachers when applying Communicative Language Teaching (CLT) in second language instruction. CLT is widely regarded as one of the most effective approaches to language teaching; however, from teachers’ perspectives, it presents several practical difficulties. This approach aims to develop native-like proficiency and pronunciation while fostering the integrated development of the four language skills: reading, listening, speaking, and writing. As a result, successful implementation of CLT depends on a well-designed curriculum and appropriately selected instructional content that encourages meaningful interaction in the classroom. Despite its advantages, teachers may struggle to achieve optimal outcomes through CLT when learners show low motivation or limited interest in communicative activities. Another significant challenge arises when students fail to consistently use the target language, even though active practice is essential for language acquisition. Furthermore, translating theoretical CLT principles into effective classroom practice can be difficult, particularly when implementing the prescribed curriculum and materials. These challenges highlight the complexity of applying Communicative Language Teaching in real classroom contexts.